Technology, infrastructure and enterprise trade-off: Strengthening smallholder farming systems in Tamil Nadu State of India for sustainable income and food security. (June 2022) - Varadan, R Jayakumara; Mamidanna, Sravya; Kumar, Shalander; Ahmed, SK Zamir; Jaisankar, I
The complexities of smallholder farming systems pose a challenge in demonstrating the potential benefits or risks of new technologies and policies. Using Integrated Analysis Tool, a rule-based dynamic simulation model, this study tried to improve the performance of major farming systems in the Tamil Nadu State of India. Amongst the four major farming systems viz . Black gram-based (BFS), Paddy-based (PFS), and Integrated Farming Systems (IFS) in Villupuram district and Dryland Farming System (DFS) in Virudhunagar district, IFS was found to be the most profitable and resilient based on their performance simulated for a 3-year rotation. Setting IFS as a benchmark, potential interventions were evaluated under other farming systems to improve their relative performance. The analysis allowed understanding the interactions in smallholder farming systems and the potential impact of interventions in a whole farm way considering the cash flows, cost intensity, and input-output trade-offs. While multi-bloom technology in black gram increased the net profit of BFS without much stress on input and labour, area expansion under rainfed groundnut incurred high expenditure. Trading-off paddy with maize and groundnut significantly increased the net profit of PFS but replacing sugarcane with tapioca and turmeric was not remunerative. Improved livestock management practices have substantially increased the net profit of DFS wherein crop yield could not be enhanced substantially without the prospects of good irrigation infrastructure. The irrigation endowed PFS has achieved 90% performance, whereas the water-starved BFS and DFS could achieve only 65% performance of IFS. We conclude that agricultural policy must not only focus on potential interventions that are profitable but also consider what is acceptable to the farmer, considering synergies and trade-offs between competing resources at the farm level.